2007
DOI: 10.1017/s0007114507749218
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nutritional status on the outcome of Indian patients undergoing neurosurgical shunt surgery

Abstract: Undernutrition is common in surgical patients, is frequently unrecognised and is strongly associated with adverse outcomes such as high rates of complications and mortality, worsening functional status and prolonged hospitalisation. Owing to the associated infection and symptoms such as repeated vomiting, a high prevalence of undernutrition is expected in hydrocephalus patients, which may contribute to their poor surgical outcomes. The aim of this study was to evaluate the influence of preoperative nutritional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…The profile of chronic diseases of the Brazilian population, the aging population and the increase in the incidence of cancer may justify the occurrence of brain neoplasm as the main cause found in elective surgeries. Although the literature describes different degrees of severity in neurosurgical patients in the ICU, the present study did not observe significant differences in the score of the SOFA and GCS scales, data consistent with the Jain study in 2007 (17) .…”
Section: Discussionsupporting
confidence: 90%
“…The profile of chronic diseases of the Brazilian population, the aging population and the increase in the incidence of cancer may justify the occurrence of brain neoplasm as the main cause found in elective surgeries. Although the literature describes different degrees of severity in neurosurgical patients in the ICU, the present study did not observe significant differences in the score of the SOFA and GCS scales, data consistent with the Jain study in 2007 (17) .…”
Section: Discussionsupporting
confidence: 90%
“…Patients with better nutritional status had good ETV success rates compared to patients with malnutrition, although this difference was statistically insignificant. Jain et al, [15] in his series of patients with VP shunt, found better results in patients with good nutritional status compared to those with poor nutritional status. [15] The radiological recovery rate, within 3 weeks, was only 52% in this series; similar to the observations (55.6%) in the series by Singh et al [5] A decrease in the size of ventricle occurs very slowly after ETV.…”
Section: Discussionmentioning
confidence: 95%
“…Prospective studies in specialized settings which have evaluated nutritional status for its role in recovery have seen malnutrition in 53–59% of admitted patients. However, in these specialized settings it is likely that the underlying disease contributed further to the undernutrition and hence a large proportion of patients had malnutrition [ 22 , 23 ]. A systematic review on malnutrition in adult admitted patients in the UK and European countries demonstrated that more than half of patients at risk for malnutrition were missed and hence did not receive care relevant to nutrition [ 24 ].…”
Section: Discussionmentioning
confidence: 99%